The Effect Of Brand Ambassador On Bicycle Purchase Decisions - Yazid, Kusmawati; Kusmaedi, Nurlan; Rahely, Berliana (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The purpose of this study was to determine the influence of brand ambassadors on bicycle purchasing decisions. This research is a quantitative descriptive research with the type of survey research. The population in this study are consumers who buy polygon bicycles at YZKUZMA Bike Gallery, Cimahi City. The sampling technique used was convenience sampling/accessible sampling (samples) as many as 80 people. Then the data was processed using SPSS version 25 software using simple regression analysis. Based on the results of data analysis, it is known that the t test results have a significance value less than 0.05 (sig < 0.05), so it can be concluded that brand ambassadors partially have a significant effect on bicycle purchasing decisions. In addition, an R Square value of 0.306 or (31 percent) was obtained. This shows that 31 percent of the purchasing decision variables can be explained by the brand ambassador variable, while the remaining 69 percent by variables outside the study. These results show that the brand ambassador factor is not the only factor that influences consumer purchasing decisions given the complex nature of purchasing decisions and tends to fluctuate. Purchasing decisions are also influenced by various factors that are no less important, namely the need, brand, purchase channel and time of purchase. so that this research is expected to be used as a reference for companies in optimizing the role of brand ambassadors and other factors that will have a positive impact on consumer purchasing decisions.